Kryptowährungen: Ein Problem für die Geldpolitik? - Andreas Hanl; Jochen Michaelis (Philipps-University Marburg, School of Business and Economics, 2017)
– Cryptocurrencies such as Bitcoins may revolutionize the financial system by at least partially replacing intermediaries such as central banks and commercial banks. The blockchain technology enables users to transact on a peer-to-peer basis. This imposes a serious threat on the financial intermediaries as well as on monetary policy authorities. In this paper, we examine how well cryptocurrencies fulfill the functions of a fiat money and discuss the comparative advantages of cryptocurrencies. We proceed by exploring the implications of digital currencies for the concept and conduct of monetary policy.
Keywords: E42; E52; 330; Bitcoin; Kryptowährung; Geldpolitik